Free Induction Decay, Spin Echo Signals, Pure Superradiance, and Rabi Oscillations from Spin Triplet States in Zero Constant Magnetic Field: Application of Single Transition Operators - Fokina, Nathalie P.; Elizbarashvili, Maia O. (Scientific Research, New Technologies and Applications Vol. 4, 2024)
The present study highlights free Induction Decay, Spin Echo Signals, Pure Superradiance, and Rabi Oscillations from Spin Triplet States in Zero-Constant Magnetic Field. Anisotropic dynamics of the spin-triplet states (STSs) in single crystals with the zero fields splitting (ZFS) of their levels by the axially asymmetric Hamiltonian is investigated in zero constant magnetic fields (ZF) under the action of the canonically oriented varying magnetic fields. The equations of motion for single transition operators (STOs) corresponding to the definite transition of ZFS are derived. The obtained equations written in terms of one averaged equation for STO vector appeared to be a particular case (for STS) of the universal equation of Feynman et al, which is valid for any kind of perturbation affecting only two levels of any quantum mechanical system. As well as that, our equation is analogous to the Bloch equation without decay for the usual magnetization components of the Zeeman system in a constant magnetic field and a transverse to its varying field. However, the motion of the observable macroscopic sample magnetization, which follows from our equations, has quite a different character than that of the motion of the STO vector. Here, in terms of this magnetization the signals of the free induction decay, of the two-pulse spin echo, the parameters of the pure superradiance and Rabi oscillations are calculated in ZF. Rabi oscillations observable both in the frequency domain and in the time domain are investigated classically in the linear approximation. At that, a variety of two-level systems (spin transitions, magnons, atoms, molecules, excitons and so on) can act as emitters. The “fork” effect is predicted for normal decay at the decreasing of the value of the spin-photon coupling, in contrast to the known “fork” effect of normal frequencies with increasing spin-photon coupling.